Multifactorial influences of childhood obesity - Wee Bee, Suan; Yeow Nyin, Ang; Bee Koon, Poh; Mohd Noor, Ismail (2013)
Obesity is the result of complex interactions of multiple factors that have gradually led to enduring changes in lifestyles, and thus, creating a global epidemic of major health concerns. The roles of genetics and the environment are vital and need to be explored to further our understanding of the etiology of childhood obesity. This review critically looked at published reports over the past decade on factors that are unmodifiable, such as genetics, ethnic differences, gestational weight and intrauterine conditions; as well as modifiable factors, such as socioeconomic status, diet, physical activity, sleep, and parental determinants. With the worldwide increase in prevalence of pediatric obesity over the past several decades, it is imperative that we understand the root causes of obesity in order to arrest the rising trend through better prevention and intervention strategies